Application of Hardening for WLAN Security Optimization in the IT Services Division at PT PUSRI - Muhammad Reihan Pratama (Institute of Information Technology and Social Science (IITSS), 2025)
Computer networks typically use two primary transmission methods: wired and wireless networks, commonly referred to as Wireless Local Area Networks (WLANs). In WLAN implementations, the standard security mechanism frequently adopted is Wi-Fi Protected Access 2 Pre-Shared Key (WPA2-PSK), which relies on an SSID and password. Despite this security mechanism, criminal activities such as unauthorized access and network intrusions continue to occur. Therefore, it is essential to enhance network security to ensure that WLAN environments remain secure and capable of minimizing potential risks to users. This study aims to improve and optimize WLAN network security by conducting vulnerability scanning using Nessus to assess existing security conditions, followed by the implementation of hardening techniques to strengthen and obscure vulnerabilities. Hardening includes several approaches such as applying raw firewalls and firewall filters, restricting ports and services, disabling unnecessary services, disabling the MikroTik Neighbor Discovery Protocol (MNDP), and implementing port knocking as an additional layer of protection. The findings indicate that applying vulnerability scanning alongside a structured hardening strategy significantly minimizes identified risks and enhances the overall resilience of the WLAN network against intrusions and security threats.